DETERMINAÇÃO DE Pb (II) EM MICROEMULSÕES DE BIODIESEL USANDO ELETRODO DE FILME DE BISMUTO PELA VOLTAMETRIA DE REDISSOLUÇÃO ANÓDICA NO MODO ONDA QUADRADA - Carvalho, Paulina Andréa Viana de (2011)
Biodiesel has been studied as an alternative in reducing emissions of gases, however, it is necessary to analyse and to assure the quality of this biofuel because of the presence of possible contaminants, such as metals, which degrade the biodiesel during the storage process besides possible emissions of waste from its production. To analyze the Pb (II) into biodiesel, the sample was prepared by means of microemulsion by mixing biodiesel, nitric acid and propan-1-ol, The advantage in the use of microemulsões in vegetable oils is that analyses become faster, avoiding random errors, since it eliminates extraction steps and pré-concentração during the preparation of the sample.This work was intended to determine Pb (II) in the sample of biodiesel, through the preparation of the sample in microemulsion, and analyze by Anodic voltammetry in square wave mode by film of bismuth (BiFE). The technique used for determination of analyte was differential voltammetry in square wave mode because it is a sensitive technique and has low cost. The bismuth film was used as an alternative because of its low toxicity, besides forming alloys with many metals. In this proposed procedure, several experimental parameters have been optimized, showing the best conditions, such as potential deposition ( -1,2 V), time of deposition (60 s), study of the composition of the reaction mixture (8 mL of electrolyte mixture: 2 mL microemulsion) and the possible influence of Zn (II), Cd (II) and Cu (II) in the current peak Pb (II) ion. The optimized parameters for technique were: frequency of 10 Hz and scan rate 60 mV s-1 bismuth electrode exhibited a good linearity in the concentration of Pb (II) in the range 2,5x10-9 - 7,5x10-9 mol L-1 (R2 =0,997- 0,999) for samples using microemulsions; LD of 2, 96x10-10 mol L-1 besides a good reproducibility (CV = 5,23-3,97%) to concentrations of Pb (II) 2,09x10-9 mol L-1 and 3,35x10-9 mol L-1 (n = 3 measures), respectively. Through the results obtained, it was found that the methodology applied is suitable for analysis of metal in the array of study.